The level of environmental awareness among sixth graders’ students in light of some variables Preliminary study in the basic education schools Lattakia City (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of the research was to investigate the level of environmental awareness among sixth graders’ students in light of the gender variables and the cultural level of the mother.In order to achieve this goal, the descriptive approach was used, and the "environmental awareness" scale was prepared. After verifying its validity, it was distributed to a sample of 140 students and students from the sixth grade school in Lattakia in 2017/2018.The results showed that the level of awareness among the sixth grade students was average. There were no statistically significant differences among the sixth grade in terms of environmental awareness due to sex, while there were statistically significant differences due to the cultural level of the mother in favor of students whose mothers have university degrees.